Reality counseling: Overcome anxiety and build self-confidence in thesis completion - Yulianti, Dewi; Aulia, Fitri; Mahyatun, Baiq; Marfuatun, Marfuatun; Alengka, Novi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Anxiety in completing theses is a common issue faced by final-semester students. This anxiety arises from various challenges, such as difficulty focusing on the thesis topic, trouble writing the background of the problem, confusion about thesis structure and content, limited mastery of theory, weak research methodology skills, and ineffective communication with supervisors. These issues often lead to anxiety and low self-confidence among students. One effective intervention to address these challenges is group counseling with a reality approach. This study employed a pre-experimental quantitative method with a one-group pretest-posttest design. After using purposive sampling, six students meeting the criteria for group counseling participants were selected. Data were collected through questionnaires and analyzed using a t-test. The results revealed a significant effect of the reality approach in reducing anxiety and boosting self-confidence, with a t-count value of 24.413, exceeding the t-table value of 2.571. In conclusion, group counseling with a reality approach is proven effective in alleviating anxiety and improving self-confidence in final-semester students working on their theses.